The predictive value of the systemic immune-inflammatory index for left atrial appendage thrombus in non-valvular atrial fibrillation - Koca, Fatih; Levent, Fatih; Sensoy, Baris; Tenekecioglu, Erhan (Biomedical papers, 2023)
Objective. The systemic immune inflammatory index (SII) has prognostic value in cardiovascular diseases. The aim of current study was to investigate whether or not left atrial appendage (LAA) thrombus could be predicted by SII in patients with non-valvular atrial fibrillation. Method. The study included 525 patients newly diagnosed with non-valvular atrial fibrillation, who had not previously had anticoagulant treatment (50.7% male, mean age 62.94 extpm10.79 years). All patients underwent transoesophageal echocardiography. Results. LAA thrombus was observed in 86 patients (16.4%). In the ROC curve SII had a good diagnostic power in predicting LAA thrombus (AUC: 0.760, 95% CI: 0.703-0.818, P<0.001). In the multivariate regression analysis, diabetes (Hazard ratio: 2.264, 95% CI: 1.169-4.389, P=0.015), LAA emptying rate of <20 cm/s (Hazard ratio: 59.347, 95% CI: 25.397-138.680, P<0.001), and SII value of >750 (Hazard ratio: 4.291, 95% CI: 2.144-8.586 P<0.001) were determined as independent predictors for LAA thrombus. A poor correlation was found between SII and the CHADS2 VASc score (r=0.239, P<0.001) Conclusion. The SII, a practical and easily obtained test, can be used as a predictor of LAA thrombus in patients with non-valvular atrial fibrillation, and to decide on the anticoagulant treatment.
Keywords: systemic immune-inflammatory index; left atrial appendage thrombus; atrial fibrillation; diabetes